2019
DOI: 10.1371/journal.pone.0224092
|View full text |Cite
|
Sign up to set email alerts
|

Exercise intensity-dependent effects of arm and leg-cycling on cognitive performance

Abstract: Physiological responses to arm and leg-cycling are different, which may influence psychological and biological mechanisms that influence post-exercise cognitive performance. The aim of this study was to determine the effects of maximal and submaximal (absolute and relative intensity matched) arm and leg-cycling on executive function. Thirteen males (age, 24.7 ± 5.0 years) initially undertook two incremental exercise tests to volitional exhaustion for arm-cycling (82 ± 18 W) and leg-cycling (243 ± 52 W) for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Conversely, cognitive performance after high-intensity exercise is heterogeneous; with improvements (Winter et al, 2007;Luft et al, 2009;Thomson et al, 2009;Griffin et al, 2011;Etnier et al, 2016;Hwang et al, 2016;Hill et al, 2019;Coco et al, 2020a;Loprinzi et al, 2021), impairments (Fery et al, 1997;McMorris et al, 2005;Coco et al, 2009Coco et al, , 2020aThomson et al, 2009;Zimmer et al, 2017;Hill et al, 2019), and no changes (Travlos and Marisi, 1995;Brisswalter et al, 1997;Kamijo et al, 2004a,b;Luft et al, 2009;Griffin et al, 2011;Chang et al, 2017;Sudo et al, 2017;Du Rietz et al, 2019;Marin Bosch et al, 2021) reported within the literature. These findings suggest that cognitive performance after high-intensity exercise appears to be dependent on experimental design (see below).…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, cognitive performance after high-intensity exercise is heterogeneous; with improvements (Winter et al, 2007;Luft et al, 2009;Thomson et al, 2009;Griffin et al, 2011;Etnier et al, 2016;Hwang et al, 2016;Hill et al, 2019;Coco et al, 2020a;Loprinzi et al, 2021), impairments (Fery et al, 1997;McMorris et al, 2005;Coco et al, 2009Coco et al, , 2020aThomson et al, 2009;Zimmer et al, 2017;Hill et al, 2019), and no changes (Travlos and Marisi, 1995;Brisswalter et al, 1997;Kamijo et al, 2004a,b;Luft et al, 2009;Griffin et al, 2011;Chang et al, 2017;Sudo et al, 2017;Du Rietz et al, 2019;Marin Bosch et al, 2021) reported within the literature. These findings suggest that cognitive performance after high-intensity exercise appears to be dependent on experimental design (see below).…”
Section: Resultsmentioning
confidence: 99%
“…More recent empirical research into the inverted-U effect fails to clarify the picture, with somewhat equivocal results being demonstrated (Chang et al, 2019;Ligeza et al, 2018;Smith et al, 2016). Although the inverted-U effect has limited support, the reviews provide strong evidence for an improvement in cognitive performance from rest to moderate intensity exercise, The findings of studies carried out since these reviews have generally provided more equivocal results with some showing facilitation during and after moderate intensity exercise (Bae and Masaki, 2019;Chang et al, 2019;González-Fernández et al, 2017;Hsieh et al, 2018;Kujach et al, 2018;Labban and Etnier, 2018;Wu et al, 2019) but not others (Chacko et al, 2019;Hill et al, 2019;Lefferts et al, 2019;Winneke et al, 2019). Overall, however, there remains strong support for the conclusion that moderate intensity exercise facilitates performance.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the modality of movement, differences have already been described for running and cycling and should be evaluated for upper-body movement as well (Hill et al, 2019). Indeed, running requires greater coordination and control of body movement compared with cycling, and thus, it is plausible that a greater allocation of physiological and psychological resources is required (Lambourne & Tomporowski, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Upper-body movement during EVA, which allocates different muscle groups and less muscle mass, might produce quite different effects than running and cycling in the laboratory. This has not yet been investigated underwater; however, one study showed comparable positive effects of arm cycling with leg cycling on EFs (Hill et al, 2019).…”
Section: Introductionmentioning
confidence: 99%